Green Roofs in Portugal – A challenge on the reduction of energetic consumption - Matos, Rute Sousa (2012)
In 2030, Earth will have completed its urban revolution. Planetary urbanization imposes a time and space separation and attributes to each one a complete autonomy that changes the principles that enable us to move or stop. In these disintegrated times and decomposed and re-configurated territories, the homo urbanus must find its sense. As a consequence of this research as well as the current crisis we are living, we have an increasing awareness of in professionals connected with urbanism and the city to the environmental issues. In Portugal, there are ongoing debates between authors, for the reduction of fossil fuels and for the promotion of various forms of renewable energies. Promoting all types of energy efficiency is crucial, among which the importance of the space organization of the activities, the construction, urbanism and the consequences for the urban climate, the health and the quality of the environment, needs to be alluded. One important regulator is the heat exchange between soil and atmosphere through water evaporation, the soil impermeabilization, not only prevents rain water infiltration but also lowers soil humidity, as well as it changes the energy exchanges received from the sun and the surrounding environment. The effect is reinforced or attenuated, depending on the buildings geometrics, their relative position, thermal inertia and its exterior cover, primarily façades and coverings. In this presentation we intend to demonstrate that the practice of green roofs in cities is an added value in supporting and maintaining biodiversity in urban areas, working as a way to restore lost habitats due to the increased construction. It is also intended to demonstrate the relevance of green roofs in regulating global climate, revealing substantial variations in “Runoff”, as well as variations caused by thermal “Heat Island Effect”, occurred in large cities. The impermeabilization covered with green vegetation also brings benefits to the buildings, especially in increasing the time span of the roof and reducing heat within them. The temperature decreases in the cities and consecutively from inside the buildings bringing great benefits in terms of energy savings, contributing to the protection of the environment and a more efficient use of the resources. It is also our aim to prove that green roofs are the key to ensuring the continuum naturale in urban space, as such; they should be considered and integrated in the ecological structure of the cities.